Healing-Informed Social Justice Mathematics: Promoting Students' Sociopolitical Consciousness and Well-Being in Mathematics Class. (November 2019) - Kokka, Kari
Using an ecological approach to trauma-informed care and radical healing, this case study explores how one Title I public middle school mathematics classroom offered students opportunities to engage in healing practices through the use of Social Justice Mathematics. Findings indicate that students identified their emotions, engaged in structural analyses of local social issues, and expressed plans to take action. This study suggests the possibility of using a Healing-Informed Social Justice Mathematics approach to support development of students' sociopolitical consciousness, mathematics learning, and well-being.